Tak zwana prawotwórcza decyzja sądowego stosowania prawa: [The so-called legally creative decision of enacting judical law] (Studia Prawnicze / The Legal Studies, 2023)
The aim of this work is to state the relation between the creation and the enaction of judical law. The question may be considered from four points of view: the normative, the descriptive, the theoretical and the evaluating. The article does not include the latter for it is the result of the author’s analysis method.Theoretical analysis indicating that it is impossible to state the difference between logical sentences and norms at the language structure level but at the individual speech acts level is especially important. The characteristics of an utterance at the level of speech requires the consideration of the problems of a pragmatic background, which consists, on one hand, of the elements of a definite situation, and on the other hand, the cultural rules contributed by the participants of the communication act. The legal norm is primarily distinguished by the cultural rules used in a definite act of communication. The point number four of the work is devoted to the attempt of determining these rules. The author confined his considerations only to the investigation of the legal culture, trying to formulate only a partial definition (contextual and necessitive) of law creation activity.The catalogue of conditions necessary to fulfill this activity in our legal culture consists of five rules: power, norm generality, competence, procedure and normative novelty. It turns out, that all these, conditions may perform, in certain circumstances, three kinds of decision of the Supreme Court: the guide lines of jurisdiction and the judicial practice, the Superior Court’s resolutions and the legal principles.